Social validity for work ability assessments and official decisions – clients' experiences. (13th November 2019) - Karlsson, E; Sandqvist, J; Ståhl, C
Abstract: Background: Professionals need to be able to express what is at stake during the decision-making process and the discrepancy between formal rules and practical rationality need to be bridgeable and transparent for outsiders. Investigations of social validity for work ability assessments are rare. However, the concept can provide valuable information upon the acceptability and comprehensibility of procedures and how professionals can increase clients' participation. The purpose of this study was to investigate social validity for work ability evaluations within the sickness insurance system and the official decisions they lead to. Methods: This was a longitudinal qualitative study using telephone interviews and files from the Swedish Social Insurance Agency. Clients (n = 30) were interviewed after their participation in a work ability evaluation as well as after receiving an official decision upon eligibility for sickness benefits. Data was analyzed using a deductive content analysis. Results: Preliminary findings show that clients' comprehensibility of the different tests and their composition were depending on whether the specific tests were perceived as clearly related to the clients' difficulties and what information they had received. In order to receive a fair description of the client's work ability, clients state that the work ability evaluation needs to be individually adapted and that the standardized structure is not relevant for all. What is acceptable and fair to one client could be unacceptable to another, depending on what arguments and information case-managers and evaluation professionals provided. Conclusions: Authorities need to express and motivate the reasons for a diverse range of steps during clients sick-leave process, not only regarding official decisions. Social validity for work ability evaluations is depending on the provided information and the applicability to the clients' situation. Key messages: Social validity is depending on the provided information and the applicability to the clients' situation. Authorities need to communicate clearly with clients through the whole sick-leave process.